COVID-19 and labour in agriculture: Economic and productive impacts in an agricultural area of the Mediterranean - Cortignani, Raffaele; Carulli, Giacomo; Dono, Gabriele (Italian Journal of Agronomy, 2020)
Social distancing and mobility restrictions adopted in Italy to deal with the COVID-19 emergency can also alter the operating conditions of the Italian agricultural labour market. The restrictions can limit the movement of temporary labour that is already on the national territory and can prevent the arrival of other foreign workers to be engaged mainly in the harvesting of crops. In Italy, temporary workers support diverse farming activities and are mainly young immigrants engaged in working relationships characterized by extreme flexibility. They must be available for very different tasks, interacting with multiple farms and moving between different areas of the country, generally based on the succession of the harvesting calendars of the main crops. Reducing the mobility of this workforce on the national territory decreases its availability in local labour markets with worrying damage to agricultural production. This paper analyses the possible impact of this labour availability reduction in a farming area of Southern Italy (Centre-West Sardinia), where various farm types operate, with diverse productive orientations. An economic model estimates this impact on production and income based on the structural characteristics of these farm types, among others own farm labour endowment, as well as on the technical requirements of the productive processes, including labour needs. The model considers the expectations of farmers on the temporary labour availability and identifies the possible adaptations that can be undertaken to better contrast the reduction generated by the constraints to the mobility of individuals in the COVID-19 crisis. These adjustments result in changes in income levels, as well as employment in the single farm types and the area as a whole. There is a strong, albeit very diversified, impact on the types of farms. Significant reductions in income are found in the types that heavily depend on temporary labour for certain crop operations, especially harvesting. These effects are generated despite these farms change their activities, expanding some crops to make better use of their family labour and permanent employees. The less profitable types of farm, therefore even less able to attract external resources, considerably worsen their conditions; this would aggravate the social and environmental balance of the areas in which they operate, which are also the most marginal in the study area. Highlights - The measures taken in Italy to deal with the COVID-19 emergency modify the conditions of the agricultural labour market restricting the mobility of temporary labour. - Temporary workers support many farming activities in Italy and are mainly young immigrants engaged in working relationships characterized by extreme flexibility. - An economic model estimates the possible impacts of this labour availability reduction in a farming Mediterranean area of Southern Italy, where different farm types operate. - The farm types that heavily depend on temporary labour for certain crop operations, especially harvesting, face appreciable income level reductions. - Farm types with lower profitability are also notably endangered, with serious implications for the social and environmental balances of the marginal areas in which they operate.